Trajetórias escolares de adolescentes em conflito com a lei: aspectos pessoais e contextuais - Machado, Jéssica Costa (2018)
This masters dissertation approaches the relationship between school aspects and the practice of juvenile offense in order to understand both the school factors that are associated with the development of conflicts with the law and those that can be favorable to the reconstruction of life projects during and after the fulfillment of socio-educational measures. This dissertation comprises two studies, presented in the format of articles that will be submitted for publication. The first study investigated the school trajectories of adolescents in conflict with the law before, during and after the intervention of the juvenile court system through a systematic review of the literature on articles published in the Eric, Lilacs, Pepsic, PsycInfo and Scielo database from 2013 to 2018. The studies showed that the school trajectory of the adolescents who commit juvenile offense is marked by difficulties of connection with school, school-year repetition, age/school-grade discrepancy, indiscipline, school failure, turnover, school dropout, and school quitting. During the intervention of the juvenile court system, schooling and professionalization involved mainly providing individualized attention and investing in the relationship between educators and adolescents. After the intervention, the studies showed that the adolescents built life projects related to education and professionalization, but presented more severe school difficulties and lower possibilities to finish high school and college. The second study aimed to know the perception of adolescents in conflict with the law on personal aspects (self-esteem and self-efficacy) and school variables (relationship with school, schooling, school expulsion and school failure). Participants were 73 male adolescents who underwent socio-educational measures, aged between 12 and 20 years (M=16,69, SD=1,50), who answered the Brazilian Youth Questionnaire (short version, with 47 items). Descriptive and inferential analyses were performed, identifying that most of the adolescents had already failed school and more than half had already been banned from school. Even with this history, they showed a good relationship with school and high levels of self-esteem and self-efficacy. Therefore, the importance of promoting and maintaining positive relationships between adolescents and school is emphasized, since school factors and especially the link with school are important aspects for preventing and overcoming conflicts with the law in adolescence. In addition, valuing personal aspects of these adolescents, such as self-esteem and self-efficacy, should be considered in interventions with this public, especially in favor of more positive school trajectories and the construction of life projects that promote educational advancement and qualification for insertion in the job market.